Which Way Forward Indian Missions? : A Critique Of Twenty-five Years, 1972-1997 - Rajendran, K. (Krishnasamy) (Edinburgh : SAIACS Press, 1998)
Includes bibliographical references (p. [249]-260) and index. Rs160.00
Keywords: Missions -- India; India -- Church history; Indigenous church administration -- India